Feasibility and safety of minimally invasive R1 vascular surgery for hepatocellular carcinoma: a cohort study - Abdelhadi, Schaima; Şandra-Petrescu, Flavius Ionuţ; Vassilev, Georgi; Birgin, Emrullah; Rahbari, Nuh Nabi; Reißfelder, Christoph (Surgical endoscopy and other interventional techniques, 2025)
Background: In recent studies addressing colorectal liver metastases and HCC, R1 vascular surgery has demonstrated safety and oncological adequacy. Recognizing that patient prognosis after liver surgery for HCC depends more on preserving an adequate future liver remnant than on the width of the surgical margin, this surgical approach has achieved rising interest. However, data for its feasibility and safety for minimally invasive approaches for HCC resections are limited. Therefore, the aim of our study was to determine the feasibility and safety of minimally invasive R1 vascular surgery for HCC. Methods: Consecutive patients who underwent curative hepatectomies between April 2018 and May 2023 were identified from a prospectively collected institutional database. Intraoperative ultrasound was performed to guide the resection, confirm the preoperative finding regarding the tumor’s relation to the main vessels, and exclude any undetected vascular invasion or additional lesions. Postoperative complications were graded according to the Clavien-Dindo classification. Results: Among 58 patients included, 22 (38%) underwent minimally invasive R1vasc surgery for HCC and 36 (62%) non-R1vasc surgery. In the MI-R1vasc surgery group, there were significantly more infiltrated liver segments (2 vs. 1, p = 0.04) and a shorter tumor distance to the main hepatic veins (5 mm vs. 21 mm, p < 0.001) and Glissonean pedicles (4 mm vs. 26 mm, p < 0.001) than in MI-non-R1vasc surgery group. The comparisons of the type of surgical resection revealed similar findings between the study groups, with non-anatomic resections and segmentectomies being the most frequently performed resections. The median blood loss (600 ml vs. 500 ml, p = 0.41), operative time (264 min vs. 231 min, p = 0.13), and R1par resection rate (5% vs. 3%, p = 0.72) were comparable in both groups. Other intra- and postoperative outcomes were also comparable between the two groups. Conclusion: Minimally invasive R1 vascular surgery is safe and feasible for patients with Hepatocellular Carcinoma.